2010
DOI: 10.1089/ars.2009.2502
|View full text |Cite
|
Sign up to set email alerts
|

Early Neural and Vascular Dysfunctions in Diabetic Rats Are Largely Sequelae of Increased Sorbitol Oxidation

Abstract: These experiments were undertaken to assess the importance of cytoplasmic (c) sorbitol oxidation versus mitochondrial (m) pyruvate oxidation in mediating neural and vascular dysfunction attributable to hyperglycemia in diabetic rats. Increased oxidation of sorbitol is coupled to enzymatic reduction of free oxidized NAD(+)c to reduced NADHc, manifested by an increased ratio of NADH to NAD(+)c. Likewise, increased oxidation of pyruvate is coupled to reduction of NAD(+)m to NADHm, which increases the NADH/NAD(+)m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 48 publications
(70 reference statements)
8
53
1
Order By: Relevance
“…G6PD activity was also found to be increased in the liver of Zucker diabetic rats [75]. Similarly, NADPH content in certain diabetic tissues has been reported to be elevated when compared with that in non-diabetic conditions [76], [77], [78]. Nonetheless, in our present study, we found that NADPH level declined in diabetic lung (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…G6PD activity was also found to be increased in the liver of Zucker diabetic rats [75]. Similarly, NADPH content in certain diabetic tissues has been reported to be elevated when compared with that in non-diabetic conditions [76], [77], [78]. Nonetheless, in our present study, we found that NADPH level declined in diabetic lung (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…Two groups implicated increased activity of the second enzyme of the sorbitol pathway, sorbitol dehydrogenase (SDH), in activation of the superoxide-generating enzyme, NAD(P)H oxidase [61,62]. Note, however, that these findings are not consistent with other reports describing 1) an important role of AR rather than SDH in DPN [46, 63], and 2) exacerbation, rather than amelioration, of oxidative stress with SDH inhibition in tissues of diabetic rats [64, 65].…”
Section: Discussionmentioning
confidence: 99%
“…High [glucose] or nutrient excess leads to down-regulation of AMPK activity in several cell types [120,121] and lowers SIRT1 expression in endothelial cells [122, 123, 124••]. Finally, the diabetic state lowers the NAD + /NADH ratio in retina and nerve through increased flux through the polyol pathway and the elevated activity of sorbitol dehydrogenase [125][126][127][128].…”
Section: Nutrient Stress In Diabetesmentioning
confidence: 99%
“…Work in adult sensory neurons, primary Schwann cells, and kidney reveals that respiratory complex activity is down leading to reduced rates of mitochondrial electron transport and thus suppressed leakage of electrons [45•, 53]. However, this does not preclude diabetes-induced ROS generation from other sources, e.g., glucose metabolism through the aldose reductase pathway leading to enhanced NADPH oxidase (NOX) activity [125,135].…”
Section: Links Between Mitochondrial Dysfunction and Oxidative Stressmentioning
confidence: 99%